Dependence of resonances parameters from mass number - M. M. Pravdivy; I. O. Korzh (Âderna Fìzika ta Energetika, 2013)
Results of some previous investigations concerning definition of full sets of average resonances parameters S0, S1, , , S1,1/2, S1,3/2 for nuclei 47,9Ti, 55,8Fe, 58,7Ni, 65,4Zn, 72,6Ge, 79Se, 91,2Zr, 95,9Mo, 101,1Ru, 106,4Pd, 106Cd, 108Cd, 110Cd, 112Cd, 116Cd, 116Sn, 118Sn, 120Sn, 122Sn, 124Sn, 127,6Te, 144,2Nd has been presented and the place of these sets in the existing system of recommended parameters has been shown.